PEMULIAAN DEWI SRI DALAM AKTIVITAS DOMESTIKASI PADI DI BALI - I Wayan Sugita; I Wayan Suteja; I Nyoman Rema (Balai Arkeologi Bali, 2021)
The Balinese agricultural culture has existed since prehistoric times, with the advent of agriculture, especially rice domestication, as an important cultivation to date, gave rise to the myth of Dewi Sri. This study aims to studying the breeding of Dewi Sri in rice domestication activities in Bali, whose data sources were collected through field observations by observing archaeological remains in the form of worship media, lontar manuscripts and inscriptions. Besides being complemented by literature studies of various relevant journals, book and reports. This research has succeeded in revealing that the breeding of Dewi Sri in Bali is very unique, it can be seen from her mention of her local name, the worship media and its symbols are also influenced by Balinese local wisdom. Breeding is also carried out with prayers and ceremonies that are balanced with maintaining and caring for rice and rice field in order to achieve maximum results. Budaya agraris masyarakat Bali telah ada sejak masa prasejarah, dengan munculnya pertanian domestikasi padi sebagai budidaya penting hingga saat ini, memunculkan mitos Dewi Sri. Penelitian ini bertujuan untuk mengkaji pemuliaan Dewi Sri dalam aktivitas domestikasi padi di Bali, yang sumber datanya dikumpulkan melalui observasi di lapangan dengan mengamati tinggalan arkeologi berupa media pemujaan, manuskrip lontar dan prasasti. Selain itu dilengkapi dengan studi pustaka terhadap berbagai jurnal, buku dan laporan yang relevan. Penelitian ini berhasil mengungkap bahwa pemuliaan Dewi Sri di Bali sangat unik dapat dilihat dari penyebutan Dewi Sri dengan nama lokal, media pemujaan dan simbol-simbolnya juga dipengaruhi oleh kearifan lokal Bali. Pemuliaan juga dilakukan dengan doa dan upacara, diseimbangkan dengan memelihara dan merawat padi dan lahan persawahan, agar dapat mencapai hasil yang maksimal.